Anxious Displacements: The Representation of Gay Parenting on Modern Family and The New Normal and the Management of Cultural Anxiety. (July 2015) - Cavalcante, Andre
On popular television, parenting narratives have emerged as a dominant representational paradigm in depicting lesbian, gay, bisexual, and transgender (LGBT) subjectivities as "normal." However, I argue that the work of normalization in TV programs also operates on figures and relationships related to gay parents. I identify this secondary process as "anxious displacement" in which figures and relationships circulating around gay parents are overloaded with negatively codified social differences and symbolic excesses. This study examines the cultural work of anxious displacement in Modern Family and The New Normal by interrogating how racial excess, cultural capital, queerness, and the extreme are displaced onto characters in the gay parents' immediate world. Ultimately, anxious displacement instantiates gay parenting as culturally intelligible and legitimate, and in doing so, reproduces potential normative liabilities by reinscribing hierarchies of personhood. At the same time, anxious displacement validates gay parenting, undermines homophobia, and affirms gay masculinities.